Markers of survival and metastatic potential in childhood CNS primitive neuro-ectodermal brain tumours: an integrative genomic analysis - Picard, Daniel; Korshunov, Andrey; Pfister, Stefan (The lancet. Oncology, 2012)
Summary Background Childhood CNS primitive neuro-ectodermal brain tumours (PNETs) are very aggressive brain tumours for which the molecular features and best treatment approaches are unknown. We assessed a large cohort of these rare tumours to identify molecular markers to enhance clinical management of this disease. Methods We obtained 142 primary hemispheric CNS PNET samples from 20 institutions in nine countries and examined transcriptional profiles for a subset of 51 samples and copy number profiles for a subset of 77 samples. We used clustering, gene, and pathway enrichment analyses to identify tumour subgroups and group-specific molecular markers, and applied immunohistochemical and gene-expression analyses to validate and assess the clinical significance of the subgroup markers. Findings We identified three molecular subgroups of CNS PNETs that were distinguished by primitive neural (group 1), oligoneural (group 2), and mesenchymal lineage (group 3) gene-expression signatures with differential expression of cell-lineage markers LIN28 and OLIG2. Patients with group 1 tumours were most often female (male:female ratio 0·61 for group 1 vs 1·25 for group 2 and 1·63 for group 3; p=0·043 [group 1 vs groups 2 and 3]), youngest (median age at diagnosis 2·9 years [95% CI 2·4-5·2] for group 1 vs 7·9 years [6·0-9·7] for group 2 and 5·9 years [4·9-7·8] for group 3; p=0·005), and had poorest survival (median survival 0·8 years [95% CI 0·5-1·2] in group 1, 1·8 years [1·4-2·3] in group 2 and 4·3 years [0·8-7·8] in group 3; p=0·019). Patients with group 3 tumours had the highest incidence of metastases at diagnosis (no distant metastasis:metastasis ratio 0·90 for group 3 vs 2·80 for group 1 and 5·67 for group 2; p=0·037). Interpretation LIN28 and OLIG2 are promising diagnostic and prognostic molecular markers for CNS PNET that warrant further assessment in prospective clinical trials. Funding Canadian Institute of Health Research, Brainchild/SickKids Foundation, and the Samantha Dickson Brain Tumour Trust.